Roles of Endovascular Calyx Related Enzymes in Endothelial Dysfunction and Diabetic Vascular Complications - Li, Zhi; Wu, Ning; Wang, Jing; Zhang, Quanbin (Frontiers in Pharmacology, 2020)
In recent years, the number of diabetic patients has rapidly increased. Diabetic vascular complications seriously affect people's quality of life. Studies found that endothelial dysfunction precedes the vascular complications of diabetes. Endothelial dysfunction is related to glycocalyx degradation on the surface of blood vessels. Heparanase (HPSE), matrix metalloproteinase (MMP), hyaluronidase (HYAL), hyaluronic acid synthase (HAS), and neuraminidase (NEU) are related to glycocalyx degradation. Therefore, we reviewed the relationship between endothelial dysfunction and the vascular complications of diabetes from the perspective of enzymes.